ANALISIS KRISIS KEPEMIMPINAN PADA CALON TUNGGAL PEMILIHAN KEPALA DAERAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 100/PUU-XIII/2015 (STUDI KASUS KABUPATEN OGAN KOMERING ULU TAHUN 2020): PENDAHULUAN, KAJIAN LITERATUR, METODE PENELITIAN, HASIL DAN PEMBAHASAN, KESIMPULAN - Deka Eliyana; Aprilia Lestari; Yahnu Wiguno Sanyoto (Jurnal Ilmu Pemerintahan, 2024)
The Symptomps of One Candidates in post-conflict elections regent and deputy regent has become a big rumor since the Constitutional Court Decision which allowed single candidates in post-conflict local elections. Tthe causes one candidate phenomenon in 2020 and the implementation of the post-conflict regional election process in Ogan Komering Ulu Regency. This research results show that the threshold is a factor that limits political participation for small or independent parties, and encourages political strategies to maximize the opportunities of a single candidate. Apart from that, the practice of political dowries also influences the dynamics of candidate selection and power struggles at the local level. These two factors not only influence the candidate selection process but also have the potential to damage the integrity of democracy and inclusive political representation.